Sosialisasi Kewirausahaan dalam Upaya Meningkatakan Minat Wirausaha di Majelis Taklim Al-Karomah Metro Utara - Suci Pawiati; Harto Harto; Diky Angga Hendrawan; Dina Nadiyah Faiqoh (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
The thoughts of someone who has been formed through a long process and even become a habit and culture in society, is not an easy thing to change. There are many factors behind it, for example the level of education of the family and community. Instilling a passion for work is the most important thing in building the courage to improve welfare by exploring the abilities and skills within people to increase their income. Entrepreneurship is an alternative so that people or communities can empower their abilities by building their own business land. The purpose of this service activity is to provide socialization with entrepreneurship material. The socialization was carried out using the lecture method, providing examples through audio visuals, as well as questions and answers. The results of the community service activities are increasing knowledge of the congregation about what entrepreneurship is and instilling an entrepreneurial spirit to build productive businesses in an effort to increase income for the family Entrepreneurship assistance activities must continue to be carried out at all levels of society, especially the younger generation in order to improve the national economy and build the welfare of the community itself.. The abstract should write in italic, single space and 200 words.